Infrastructure systems for nuclear energy - Hsu, Thomas T. C. (Thomas Tseng Chuang), 1933- (West Susex: Wiley, 2014)
"Infrastructure Systems for Nuclear Energy summarizes this progress with an up-to-date reference to guide the future research and design of infrastructure systems for nuclear energy"--
.
Includes bibliographical references and index.
Keywords: Nuclear power plants -- Earthquake effects; Reinforced concrete construction -- Design and construction; Nuclear power plants -- Design and construction; Nuclear power plants -- Asia -- Case studies; Nuclear facilities -- Earthquake effects; Nuclear facilities -- Design and construction; Earthquake resistant design; TECHNOLOGY & ENGINEERING / Civil / General